Effectiveness of Ketamine Gargles in Prevention of Post-Operative Sore Throat in Patients Undergoing Endotracheal Intubation - Ali, Abid; Ahmed, Ishfaq; Ali, Kashif; Raza, Muhammad Hammad; Mahmood, Zafar; Aftab, Ali (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the efficacy of ketamine gargles versus placebo in prevention of post-operative sore throat in patients undergoing endotracheal intubation. Study design: Randomized controlled trial. Place and Duration of Study: Department of Anesthesiology and Critical Care, National Institute of Cardiovascular Diseases, Karachi from 13th April 2018 to 12th October 2018. Methodology: Eighty six patients undergoing elective pelvic or abdominal surgery under general anaesthesia of age between 18–50 years of either gender were included. Patients with preoperative sore throat in addition to asthma who require more than single attempt for tracheal-tube passage were excluded from the study. Patients were allocated into two groups (Group K and Group P). All patients were premedicated with alprazolam 0.25 mg orally 3 hours before surgery. Patients in group K was given preservative free ketamine 1 ml (50 mg) in 29 ml of drinking water whereas group P was given 30 ml drinking water on entering the operation theater and was asked to gargle with the preparation for 40 seconds. At the end of 24 hours of surgery patients were asked to mark the severity of POST pain on the scale. A score of 0-3 was considered as effectiveness. Results: The mean age of women in group K was 38.58±7.57 years and in group P was 38.21±7.33 years. Fifty nine (68.60%) were males and 27 (31.40%) were females. The efficacy (in terms of prevention of postoperative sore throat) was seen in 36 (83.72%) patients in group K (ketamine gargles) and in 22 (51.16%) patients in group P (placebo) with p-value of 0.001. Conclusion: Ketamine gargle is very effective in prevention of post-operative sore throat in patients undergoing endotracheal intubation.